1990
DOI: 10.1007/bf02187790
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplane arrangements with a lattice of regions

Abstract: A hyperplane arrangement is a finite set of hyperplanes through the origin in a finite-dimensional real vector space. Such an arrangement divides the vector space into a finite set of regions. Every such region determines a partial order on the set of all regions in which these are ordered according to their combinatorial distance from the fixed base region. We show that the base region is simplicial whenever the poset of regions is a lattice and that conversely this condition is sufficient for the lattice pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
193
0
5

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(203 citation statements)
references
References 25 publications
4
193
0
5
Order By: Relevance
“…The doublings in Theorem 1 correspond to adjoining hyperplanes one by one to form the arrangement. Björner, Edelman and Ziegler [2] showed that the poset of regions (with respect to a canonical base region) of a supersolvable hyperplane arrangement is a lattice. The proof given here of Theorem 1 provides a different proof of the lattice property, but uses several key observations made in [2].…”
Section: Theorem 1 the Poset Of Regions (With Respect To A Canonicalmentioning
confidence: 99%
See 4 more Smart Citations
“…The doublings in Theorem 1 correspond to adjoining hyperplanes one by one to form the arrangement. Björner, Edelman and Ziegler [2] showed that the poset of regions (with respect to a canonical base region) of a supersolvable hyperplane arrangement is a lattice. The proof given here of Theorem 1 provides a different proof of the lattice property, but uses several key observations made in [2].…”
Section: Theorem 1 the Poset Of Regions (With Respect To A Canonicalmentioning
confidence: 99%
“…Björner, Edelman and Ziegler [2] showed that the poset of regions (with respect to a canonical base region) of a supersolvable hyperplane arrangement is a lattice. The proof given here of Theorem 1 provides a different proof of the lattice property, but uses several key observations made in [2]. that one can always take P to be Irr(Con(L)), the poset of join-irreducibles of the congruence lattice of L. The usefulness of Theorem 4 is that it makes possible a non-inductive proof of the congruence normality of a class of posets.…”
Section: Theorem 1 the Poset Of Regions (With Respect To A Canonicalmentioning
confidence: 99%
See 3 more Smart Citations